PENERAPAN PENILAIAN BERBASIS KELAS PADA MINAT DAN HASIL BELAJAR MATEMATIKA SISWA - Widiyarti Widiyarti; L Gaya (Universitas Muhammadiyah Lampung, 2019)
This study aims to determine the effect of class-based assessment on students' interest and learning outcomes in mathematics. In addition, it can be used as consideration for teachers in an effort to increase student interest in mathematics through an assessment system that can make students more active in learning in order to improve their learning outcomes. This research was conducted by selecting research samples from the existing population of two classes, namely experimental and control, applying class-based assessment to the experimental class. The instruments used are questionnaires to measure interest in learning mathematics and tests to measure mathematics learning outcomes. The questionnaire consists of 24 statements in the form of a Likert scale and the test consists of 10 questions in the form of descriptions. Questionnaires and tests were administered at the end of the study. The results of the analysis obtained for students' interest in learning is 3.295 while for learning outcomes is 5.604.